Autosomal dominant polycystic kidney disease: the last 3 years - Torres, Vicente E. (2009)
Autosomal dominant polycystic kidney disease is the most prevalent, potentially lethal monogenic disorder. It has large inter- and intra-familial variability explained to a large extent by its genetic heterogeneity and modifier genes. An increased understanding of its underlying genetic, molecular, and cellular mechanisms and a better appreciation of its progression and systemic manifestations have laid out the foundation for the development of clinical trials and potentially effective therapies. The purpose of this review is to update the core of knowledge in this area with recent publications that have appeared during 2006–2009.